Regional Technology Spillovers: The Case of Central and Eastern European Countries - Jaanika MerikLl; Helen PoltimE; Tiiu Paas (European Regional Science Association (ERSA), 2010)
The process of European integration has introduced a valuable empirical example on the impact of economic integration on income convergence. Many empirical papers confirm the income convergence within the new member states and between the new and old members. At the same time it is found that the main contribution to economic growth in these catching-up countries comes from the total factor productivity growth (TFP), which motivates us to take a deeper look on the factors behind TFP developments. The objective of this paper is to shed light on the characteristics behind the productivity development in the new EU member countries. It may be generalised that the productivity development of a country, industry or firm is determined by two main factors: its own effort to develop new technologies and some external technology pool. The ability to internalize the latter into the own productivity growth depends again on many factors like: various technology diffusion channels as foreign direct investment (FDI); import and export; absorptive capacity and geographic proximity. There is a vast empirical literature on drivers of productivity and productivity spillovers, but up to our knowledge there is no comparative analysis on CEE countries. The CEE countries are typical middle income countries that do not devote many resources on own R&D, but due to the common market have presumably benefited a lot from the technology pool of the neighbouring high-income EU members. Our paper contributes to the literature by investigating comparatively the eight EU members with former Soviet background and controlling for geographical proximity. We compose a 2-digit NACE industry-level data set over the time-span of 1995-2007 and employ a dynamic panel data analysis methods suggested by Arellano-Bover/Blundell-Bond. The preliminary results indicate that compared to studies on high-income countries CEE countries have benefited relatively more from foreign R&D stock and this effect is the strongest for small countries. Our analysis shows also that the geographical proximity to the high-income countries matters and within the EU geographic proximity is a better technology diffusion channel than trade flows.
Keywords: O33; O47; F43; 330; R&D spillover; absorptive capacity; geographical proximity; catching-up economies